Fostering Environmental Stewardship through Mangrove Ecotourism: A Study on Gili Sulat's Educational Impact - Kurniasih Nur Afifah; Ri Yoo; Suhirman Suhirman (Faculty of Engineering and Applied Science, 2024)
This study investigates the educational impact of mangrove ecotourism in Gili Sulat, Lombok, Indonesia, against the backdrop of increasing recognition of mangrove ecosystems for their ecological significance and the role of ecotourism in promoting environmental stewardship. Given the urgent need for conservation amidst threats from climate change and deforestation, this research aims to assess how mangrove ecotourism can enhance environmental awareness and education among students, and foster a deeper understanding of sustainable practices. Utilizing a qualitative approach, the study engaged 22 fifth-semester Biology Education students from Universitas Islam Negeri Mataram, who participated in educational practicums within the Gili Sulat mangrove ecosystems. Data were collected through structured questionnaires and interviews, focusing on the students' perceptions, experiences, and the educational value derived from their interactions with the mangrove environment. The findings underscore the immersive nature of ecotourism as a powerful educational tool, offering insights into the complexities of marine biodiversity, conservation efforts, and the critical role of mangroves in coastal protection and climate change mitigation. Conclusively, the study affirms the potential of mangrove ecotourism in Gili Sulat as an effective platform for fostering environmental stewardship, suggesting the need for enhanced educational programming, community involvement, and sustainable management practices to maximize its benefits.